Selected Issues of Poland’s Demographic (In)Security - Gizicka, Dorota (Roczniki Nauk Społecznych, 2026)
Poland’s current and future situation results from a combination of several factors. One of the key factors is individual and social human resources. Demographic capital is a fundamental value that underpins many strategic aspects of a state’s development. In the case of Poland, our demographic resources in 2025 are still large. Nevertheless, due to a very low birth rate, the nation’s future in the area of human resources is going to look bleaker, or even catastrophic, perhaps. Demographic changes are taking place in several areas, heavily impacting security issues, particularly military and economic security. This is also already partly visible in primary, secondary and higher education, among others. This article attempts to outline several selected problems in this area.